Variability in foodscapes and fish growth across a habitat mosaic: Implications for management and ecosystem restoration. (March 2022) - Cordoleani, Flora; Holmes, Eric; Bell-Tilcock, Miranda; Johnson, Rachel C.; Jeffres, Carson
Highlights: Enclosure experiment provides estimates of habitat productivity and fish growth. Salmon growths vary across habitats with different hydrology, water residence time. Flood bypasses can provide good trophic conditions for enhanced salmon growth. Salmon growth is a good bioindicator of habitat productivity across the landscape. Habitat mosaic allows for higher ecosystem production and more resilient ecosystem. Abstract: Riverine ecosystems in their natural state are complex mosaics of habitats whose conditions vary across space and time as landscape features filter prevailing hydrologic forcing. Yet, through anthropogenic alteration many large river systems have become simplified through the construction of levees and dams that reduce lateral connectivity and flow variability. The extent to which shifts in habitat mosaics create conditions that support different trophic responses that manifest in differences in fish growth across the landscape remains largely untested. This is primarily due to limitations in linking habitat features, dynamic physical processes, and trophic transfer of energy to higher taxa at the landscape scale. Here, we conducted large-scale enclosure experiments across varying habitats on a fluvial floodplain as a model system to measure factors that influence habitat-specific growth rates in multiple Chinook Salmon ( Oncorhynchus tshawytscha ) stocks important to fisheries and of conservation concern. Using an ecosystem approach, we reveal that landscape context, water residence time, and habitat type (agricultural, wetland, river channel) result in different hot-spots of primary and secondary food production. This variation in the aquatic foodscape resulted in significant variation in salmon growth rates and ultimate size and morphology across the landscape. Floodplain habitats generally exhibited higher water residence times as highlighted by higher specific conductance, salinity, and chlorophyll-a values. Pelagic invertebrate abundance was 10 to 100 times more abundant in the off-channel habitats compared to the river channels. The average daily growth rates of the juvenile Chinook Salmon ranged from 0.15 mm day −1 and 0.01 g day −1 in the riverine habitat to 0.55 mm day −1 and 0.07 g day −1 in the off-channel habitat. These data were used to build mixed effects models that showed the influence of chlorophyll-a concentration, water temperature and pelagic invertebrate composition on fish growth across locations throughout the experiment. As landscapes become increasingly simplified there is increased risk of losing the mosaic of habitats necessary to achieve enhanced fish growth and phenotypically diverse and sustainable salmon populations. This in-situ experimental and modeling approach can be applied to other systems to develop ecosystem indicators such as habitat-specific fish growth rates to manage landscapes and processes to support resilient fish populations.